A less objectionable greed? Work-life conflict and unjust pay during a pandemic. (February 2021) - Schieman, Scott; Narisada, Atsushi
Abstract: Perceptions of unjust pay represent a central feature in research on distributive justice. Prior studies document that work-life conflict (WLC) is a strong predictor of unjustly low pay. We extend that work by asking: Did the social and economic changes associated with the coronavirus pandemic 2019 (COVID-19) modify the relationship between WLC and perceptions of unjust pay? In September 2019, we collected data from a nationally representative sample of workers to profile the quality of work and economic life. Then, during a critical period of widespread economic and social shockwaves, we re-interviewed these same study participants in May 2020 to evaluate change. We observe that the strong positive association between WLC and unjustly low pay decreased overall in the population—but the strength and direction of that association differed significantly across several dimensions of social stratification. Specifically, we found a weaker relationship among visible minorities, younger workers, and individuals with lower socioeconomic status. We interpret these patterns as suggesting that—at least among more vulnerable groups—the "greed" represented in the process of work interfering with non-work was unevenly experienced during peak period of the COVID-19 pandemic.